PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK PELAKU ASUSILA DALAM HUKUM PIDANA POSITIF DAN HUKUM PIDANA ISLAM - RUSMADI AKBAR; Firdaus '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Based sources of law in Indonesia is that in confectionery cases of criminal offenses committed by children. Criminal policy as a form of public reaction to the problems of delinquency prevention is done by means of penal and non-penal. Prevention efforts with approaches that exist today does have a tendency to prefer the means of repressive approach as well as the imposition of criminal sanctions in the form of imprisonment is still very prominent, although its implications may adversely affect the future growth and development of a child's psychological and physical. The purpose of this thesis, namely: First, to know and understand the accountability of child offenders in the Criminal Code Positive sacrilegious and Islamic law. Second, to know and understand the application of the effort against child offenders wanton criminal responsibility in Indonesia for the future.This research is a normative legal research is a study that discusses the principle of exercising their punishment for children who do not criminal. The data source is the primary legal materials, secondary law, and tertiary legal materials. Data collection for normative legal research used literature study method or documentary studies. Is analyzed qualitatively analyzed the data by not using statistics or mathematics, or the like.From the results of this study, there are two main things that can be inferred First, Accountability child sacrilegious offenders in Criminal Law and Islamic Law Positive conducted various forms of punishment takzir described, then one punishment for perpetrators of sexual harassment can be applied. Takzir that sanctioned forms of punishment on perpetrators of sexual abuse must be in accordance with the form of sexual harassment, and the sentence is expected to give consciousness or lessons for the perpetrator so that he did not commit sexual harassment again. Second, implementation efforts against child offenders wanton criminal responsibility in Indonesia for the future can be sanctioned absolute very essential. Connection with the crime issue of decency, the addition to the sanctions also imposed fines or flogging were imposed actors or doers.Keywords: Accountability, Criminal, Child, Actor, immoral